2017
DOI: 10.1016/j.robot.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Finger design automation for industrial robot grippers: A review

Abstract: Designing robust end-effector plays a crucial role in performance of a robot workcell. Design automation of industrial grippers' fingers/jaws is therefore of the highest interest in the robot industry. This paper systematically reviews the enormous studies performed in relevant research areas for finger design automation. Key processes for successfully achieving automatic finger design are identified and research contributions in each key process are critically reviewed. The proposed approaches in each key pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 65 publications
(119 reference statements)
0
44
0
2
Order By: Relevance
“…A large number of optimization schemes for the multifinger design have been discussed, which shows great promise to grip and manipulate objects of varying shapes (2,18). However, this active approach usually entails visual/force feedbacks; a central processor and complex algorithms to decide the gripping schemes (19)(20)(21) such as how wide the fingers should open and how much stress should be applied on the objects and where to apply it; and the complex design and integration of sensors, joints, and actuators (18,22). Besides, the multifinger gripper is incapable of dealing with thin and fragile objects (2).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of optimization schemes for the multifinger design have been discussed, which shows great promise to grip and manipulate objects of varying shapes (2,18). However, this active approach usually entails visual/force feedbacks; a central processor and complex algorithms to decide the gripping schemes (19)(20)(21) such as how wide the fingers should open and how much stress should be applied on the objects and where to apply it; and the complex design and integration of sensors, joints, and actuators (18,22). Besides, the multifinger gripper is incapable of dealing with thin and fragile objects (2).…”
Section: Introductionmentioning
confidence: 99%
“…In [4], we have highlighted that the current approaches in the field of finger design research may be classified as modular design, re-configurable design and customized design. According to the conclusion, customized design Fast Grasp Tool Design: From Force to Form Closure * M. Honarpardaz, M. Meier, and R. Haschke method are the most suitable approach for finger design automation due to their genericity.…”
Section: B Finger Generationmentioning
confidence: 99%
“…In our earlier comprehensive review [4] in finger design automation research area, we have shown that the very few proposed methods suffer two significant problems. First, the methods that are unable to handle objects with complex geometry.…”
Section: Introductionmentioning
confidence: 99%
“…For all the progress that we have seen, however, (i) robotic platforms remain best at pre-sorted, pick-andplace assembly tasks [23]; and (ii) many prosthetic users still prefer simple designs like the revered whole-or split-hook designs originally developed centuries ago [24,25].…”
Section: Introductionmentioning
confidence: 99%